Confissão e autoficção na obra de Reinaldo Santos Neves - Martinelli Filho, Nelson (2012)
If in 19th and 20th centuries the notion of individual had been shaken by the thoughts of intellectuals like Friedrich Nietzsche, the image of the author has been continuously controlling literary works until the mid-1960s, when it also has suffered a process of decentralization, triggered by the texts of scholars like Roland Barthes and Michel Foucault. Nevertheless, nowadays the author comes back to the stage without its late oppressive presence: after some replacing and resizing, now he participates on the planning of the traps that deceive the reader with referrals to reality that are supposedly true and that mix themselves with fictional material. In autofiction, term coined by Serge Doubrovsky in 1970, the hypothetical boundaries between reality and fiction are erased and the impasse and indecision, even in the face of texts that are self-proclaimed autobiographies, do prevail. Although autofiction has its grounds in French theoretical thought, studies on this literary practice progress in the works of Brazilian authors, as it can be seen in the rising number of texts being published; courses being held; and of researchers taking the matter into account. In this sense, this dissertation proposes to adjust its focus to the work of Reinaldo Santos Neves in an attempt to grasp what lies beyond the coincidence of the name the author, narrator and character have, an intricate game that dim the boundaries between reality and fiction, suspending the beliefs that are pretentiously maintained in autobiographical accounts. In this way, the work of Reinaldo will be analyzed in order to identify how the author biographical data commingle with fictional elements, so that this imaginary other self cannot establish bounds with a solid and stable individual, but that it will nevertheless remain inside an unresolvable zone, where the traps hind the reader of leaning on any alleged truth.